Empire forestry and its failure in the Philippines : 1901–1941 - Luyt, Brendan (2018)
From the mid-nineteenth century onwards there developed in the British colonies a distinctive set of forestry practices that came to be described as Empire forestry. These practices grew out of the same milieu as imperialism, and had their earliest expression in British India. Gregory Barton argues that Empire forestry also heavily influenced the forestry of the United States and that from there it spread to the Philippines. However, this article argues that the variant of Empire forestry developed in the Philippines was not particularly successful as its proponents failed to adequately adapt it to local social and political conditions.